The Landscape of State Anti-Abortion Legislation - Sussman, Rachel (Columbia Journal of Gender and Law, 2015)
Rachel Sussman: Thanks, everybody, for having me. I’m thrilled to be here. I spend most of my time reading bills that intend to restrict access to reproductive healthcare, and taking a break from that, stepping back and hearing from others in this environment, is really important. So I’m thrilled to be hete, thank you. To start, I’ll make a quick note about Planned Parenthood. I think we exist in a unique space with regard to advocacy. We are a healthcare provider, so we have hundreds of health centers across the country. One in five women in the United States will visit a Planned Parenthood at some point in her life.’ So our advocacy and the way we move forward, whether through litigation or public policy and legislation, first and foremost focuses on our patients and how we can serve them best.